2018
DOI: 10.1002/suco.201700094
|View full text |Cite
|
Sign up to set email alerts
|

Numerical modeling of steel–concrete composite structures

Abstract: Steel–concrete composite structures are diverse in form and are widely used in industrial and civil infrastructures. To effectively simulate nonlinear behavior of composite structures under vertical load and horizontal earthquake action, a group of material constitutive models suitable for concrete in composite structures, concrete‐filled steel tubes that consider restraining effect, steel bars, and steel plates are developed via the User subroutine to define a material's mechanical behavior (UMAT) of a large‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 17 publications
(33 reference statements)
0
3
0
Order By: Relevance
“…For all uncertainty types that enter any RC beam calculation, the elastic method is a satisfactory solution for present-day conditions [1]. Concretesteel composite structures have developed rapidly since the 1950s due to their superior performance and material advantage [2]. Generally, concrete and steel joint behaviour in an RC column and beam is unlike material science, where the direct rule of mixtures is a weighted average.…”
Section: Introductionmentioning
confidence: 99%
“…For all uncertainty types that enter any RC beam calculation, the elastic method is a satisfactory solution for present-day conditions [1]. Concretesteel composite structures have developed rapidly since the 1950s due to their superior performance and material advantage [2]. Generally, concrete and steel joint behaviour in an RC column and beam is unlike material science, where the direct rule of mixtures is a weighted average.…”
Section: Introductionmentioning
confidence: 99%
“…The steel-concrete composite structural elements are a solution that provides several advantages, such as the reduction of the element’s dimensions, the self-weight and the structural volume, the structural steel consumption, the foundation costs and also the improvement of dimensions accuracy. In recent years, several researchers have studied steel-concrete composite elements, defending their advantages and applications (Bezerra et al, 2018; Chen et al, 2019; Liu et al, 2017; Qiang et al, 2018; Rossi et al, 2020a; Rossi et al, 2020b; Xu et al, 2018; Zhou et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…They found that the addition of steel fibers is a more effective method than using a thicker steel tube for enhancing the ductility, and more advantageous in the case of higher strength concrete. Qiang et al, based on the analytical results, have proposed a section analysis method for round‐end sections, which is integrated into a fiber beam‐column model of steel–concrete composite structures in combination with the existing fiber discretization program. Comparison with extensive tests shows that the present fiber model has good accuracy and applicability.…”
Section: Introductionmentioning
confidence: 99%